Encouraging of Teacher and Educational Personnel Engagement of the Private Islamic Secondary Schools in Ao Luek District under Krabi Office of the Private Education Commission) - kongsin, phoaree; Chuanwon, Chacharin; Prasomsuk , Teerapat (Journal of MCU Phetchaburi Review, 2023)
The purpose of this study was to study the organizational engagement of teachers and educational personnel in private Islamic schools at the secondary level, Ao Luek District, under the Office of the Private Education Promotion Commission, Krabi Province. The population and data sources used in the study were teachers and educational personnel, totaling 110 people. The tools used were questionnaires. Data were analyzed using statistics, frequency, percentage, mean and standard deviation. The study found that Secondary Islamic private schools, Ao Luek District, there were 4 aspects of organizational engagement of teachers and educational personnel at a high level, ranked from the highest to the lowest, namely the factors of administrators or supervisors. , the satisfaction factor, the organizational factor and the factor of job characteristics Guidelines for developing teacher engagement and educational personnel Secondary Islamic Private School Determine a total of 38 strategies, consisting of 1. Organization Factors 14 approaches 2. Job Characteristic Factors 11 approaches 3. Satisfaction Factors 6 approaches and Executive or Supervisor Factors 7 approaches.